Meningkatkan Minat Baca Menggunakan Problem Based Learning (PBL) Berbantuan Scrapbook Berbasis Canva Materi Orang Beriman Menghargai Martabat Manusia PAKBP Kelas IX SMP Mardi Waluya Cibinong - Ridwan Barus (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
Education in Indonesia is based on the basic ideology of Pancasila and the National education system which is run by the government and the private sector. One of the improvements and innovation efforts made by the government in the education sector is by launching the Merdeka Belajar program. Catholic Religious Education and Character Education aims to help students develop Catholic faith, morals and character in accordance with the Pancasila Student Profile. In this classroom action research, the researcher focuses on the critical reasoning dimension which is based on the importance of forming strong character and mental attitudes in the younger generation, especially in facing complex global challenges. Mardi Waluya Cibinong Middle School is a school that has adequate library facilities and a strategic location in the center of Cibinong city. However, based on observation results, this school is facing the problem of decreasing student interest in reading, especially in class IX. Based on the problem conditions above, teachers can provide learning experiences by designing the learning process. The Problem Based Learning (PBL) learning method can increase interest in reading in junior high school children because this method provides students with the opportunity to choose problems that suit their interests and needs. The objectives of the research include (1) to find out how the application of the Problem Based Learning (PBL) learning method assisted by Canva-based scrapbooks can increase interest in reading and critical reasoning (2) to find out how much interest in reading students at Mardi Waluya Cibinong Middle School class IX increased after it was implemented Problem Based Learning (PBL) learning method assisted by Canva-based scrapbooks (3) to increase reading interest of class IX students at Mardi Waluya Cibinong Middle School on material about believers respecting human dignity in facing the challenges of the digital era, such as distractions from social media and gadgets. The type of research used is qualitative with a descriptive approach. Data collection techniques in this research used observation, interviews and documentation. The data analysis technique used consists of data reduction by selecting raw data into information, data presentation, namely presenting data in the form of descriptions, graphs, tables and drawing conclusions by making conclusions from research results that refer to the problem formulation. The use of the Problem Based Learning model according to the syntax which includes orienting students to problems, organizing students to learn, guiding individual and group investigations, developing and presenting results, analyzing and evaluating the problem solving process, is effective in helping increase students' interest in reading and critical reasoning. students on material about believers respecting human dignity in class IX of Mardi Waluya Middle School, Cibinong